Control of the brain microcirculation following traumatic brain injury and stroke - Jose A Rafols (Brain Circulation, 2015)
The cerebral microvessels are parenchymal branches of the brain′s penetrating vessels that include small diameter arterioles and capillaries and through which the cerebral microcirculation delivers vital metabolites to the brain. In contrast to conductance or meningeal vessels, vasomotor tone in cerebral microvessels is not dependent on the action of the sympathetic nervous system but rather on a combination of vasoreactive agents such as angiotensin, vasopressin, and purines from both brain endogenous and exogenous sources. The microvascular wall consists mainly of endothelial cells (ECs), smooth muscle cells, and pericytes (PCs) as well as the sieve-like basal lamina (BL), which together with perivascular astroglia (AS) interact dynamically to maintain the integrity and permeability of the blood-brain barrier (BBB). To ensure constant delivery of oxygen and glucose, the flow of blood through microcirculation is under autoregulatory control, both systemically and locally at the level of the microvascular wall. At the microvascular wall, endothelin (ET) and nitric oxide (NO) as well as circulating agents provide local vasopressor and vasodepressor effects that are crucial to maintain a normal vasomotor tone. Following trauma or stroke, three major pathologies occur: 1) alterations in structural integrity of microvessels and brain parenchymal cells, 2) acute edema formation, and 3) sustained hypoperfusion from vasospasm. Other pathologies that may contribute to a defective microcirculation include the formation of microthrombi and hemorrhaging, which can exacerbate the immune response. A defective microcirculation due to the loss of autoregulatory control of microvessels may contribute to the brain′s shift to anaerobic metabolism and to the formation of oxygen-free radicals, considered to be a major source of injury to nerve cells and the BBB. The diverse pathophysiologies ensuing from these events lead to nerve cell loss and poor neurological outcome. Because of these diverse pathophysiologies, monotherapeutic interventions to improve the microcirculation after trauma and stroke have had limited success both at the bench and the clinic. Recent polytherapeutic interventions aiming at improving the microcirculation as well as cell viability and neurological outcome after trauma and stroke are discussed.